Identification of Design Elements Forming Visual Perception in Mosque Spaces (Case Study: 5 Pathok Negoro Mosques): Identifikasi Elemen Desain Pembentuk Persepsi Visual Pada Ruang Masjid (Studi Kasus: 5 Masjid Pathok Negoro) - Fanani, Rizal (Universitas Aisyiyah Yogyakarta, 2024)
Human ability to recognize an object depends on how much knowledge will influence our perception, one of which is visual perception. This study aims to identify design elements that play a role in forming visual perceptions of mosque spaces. The research method used is a descriptive-qualitative method by observing and analyzing the case study of 5 Pathok Negoro Mosques. The research results show that several design elements make a difference in the visual perception of the Pathok Negoro Mosque, making it a unique characteristic that differentiates one mosque from another.